CUSUM analysis of learning curves for the head‐mounted microscope in phonomicrosurgery. (27th May 2016) - Chen, Ting; Vamos, Andrew C.; Dailey, Seth H.; Jiang, Jack J.
Abstract : Objectives/Hypothesis: To observe the learning curve of the head‐mounted microscope in a phonomicrosurgery simulator using cumulative summation (CUSUM) analysis, which incorporates a magnetic phonomicrosurgery instrument tracking system (MPTS). Study Design: Retrospective case series. Methods: Eight subjects (6 medical students and 2 surgeons inexperienced in phonomicrosurgery) operated on phonomicrosurgical simulation cutting tasks while using the head‐mounted microscope for 400 minutes total. Two 20‐minute sessions occurred each day for 10 total days, with operation quality ( Qs ) and completion time ( T ) being recorded after each session. Cumulative summation analysis of Qs and T was performed by using subjects' performance data from trials completed using a traditional standing microscope as success criteria. Results: The motion parameters from the head‐mounted microscope were significantly better than the standing microscope ( P < 0.01), but T was longer than that from the standing microscope ( P < 0.01). No subject successfully adapted to the head‐mounted microscope, as assessed by CUSUM analysis. Conclusion: Cumulative summation analysis can objectively monitor the learning process associated with a phonomicrosurgical simulator system, ultimately providing a tool to assess learning status. Also, motion parameters determined by our MPTS showed that, although the head‐mounted microscope provides better motion control, worse Qs and longer T resulted. This decrease in Qs is likely a result of the relatively unstable visual environment that it provides. Overall, the inexperienced surgeons participating in this study failed to adapt to the head‐mounted microscope in our simulated phonomicrosurgery environment. Level of Evidence: 4 Laryngoscope, 126:2295–2300, 2016